2021
DOI: 10.48077/scihor.24(5).2021.46-53
|View full text |Cite
|
Sign up to set email alerts
|

Behavior and Energy Losses of Cows during the Period of Low Temperatures

Abstract: Over the past 20 years, dairy farms in Ukraine have been actively introducing the keeping of cows in easy-to-assemble premises. However, in a moderate climate (with four distinct year seasons), the issues of microclimate, energy losses of animals and their behavior during the cold period of the year for keeping in such premises have not been fully studied. The purpose of this work was to study the influence of the heat insulation elements use of side curtains in easy-to-assemble premises during the period of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It was found that the use of side curtains made of polycarbonate produces a positive effect on the microclimate of the premises in the winter period (an increase in temperature by 3.2 • C and 8.8 • C along with a decrease in the wind speed on premises by 11.68% to 21.74% compared to those in the same premises without side curtains or with thick straw bedding). It was noted that the number of cows resting on the floor, during the lowest temperature period, increased compared to their accommodation in cow houses without the side-mounted heat-isolating panels [4][5][6]. Li Q. et al [7] performed numeric simulations of cattle management premises in order to study the influence of the eight possible operation modes of opening the side curtains installed on the walls on the microclimate and on the airflow velocity for a typical cow house premises with natural ventilation during wintertime.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the use of side curtains made of polycarbonate produces a positive effect on the microclimate of the premises in the winter period (an increase in temperature by 3.2 • C and 8.8 • C along with a decrease in the wind speed on premises by 11.68% to 21.74% compared to those in the same premises without side curtains or with thick straw bedding). It was noted that the number of cows resting on the floor, during the lowest temperature period, increased compared to their accommodation in cow houses without the side-mounted heat-isolating panels [4][5][6]. Li Q. et al [7] performed numeric simulations of cattle management premises in order to study the influence of the eight possible operation modes of opening the side curtains installed on the walls on the microclimate and on the airflow velocity for a typical cow house premises with natural ventilation during wintertime.…”
Section: Introductionmentioning
confidence: 99%